Analysis of Consumer Preferences on Mineral Water Packaging from Perspective a Product Design - Jakaria, Ribangun Bamban; Iswanto (2477 - 6165, 2024)
The bottled water market is projected to be the largest beverage category by volume worldwide. This is one of the reasons why the growth rate of the packaging industry in Indonesia is growing rapidly. However, with the increasing use of plastic as a basic material for mineral water packaging, the recycling or recycling process may be difficult to carry out so that the impact caused by plastic pollution can be minimized, so packaging materials and information on material use become important. This research needs to be carried out to find out the importance for companies to know and understand the world's efforts in campaigning to go green as a joint effort to care about the environment and the ability to create products with environmentally friendly packaging. The aim is to analyze consumer preferences for mineral water packaging designs available on the market, to the attributes attached to the product, especially the packaging materials and product information conveyed. The method used is utility analysis, the results of this research are that the observed attributes can inform and be used as recommendations for creating a packaging design that can continuously facilitate consumers and measure how important the ingredients and information on the packaging influence it. So, there are efforts to improve the design attributes of existing mineral water packaging products, to influence consumer preferences in making purchasing decisions for these products.